(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
Based on the properties of Mittag-Leffler function, the behavior of eigenvalue and the eigenfunction for a class of fractional differential equations with integral boundary value condition is discussed, and the asymptotic expression of the eigenfunction is given.